УНИВЕРСАЛЬНЫЕ МАТЕМАТИЧЕСКИЕ МОДЕЛИ m-ПУЛЬСНЫХ ВЫПРЯМИТЕЛЕЙ СО СМЕШАННОЙ RLC-НАГРУЗКОЙ В ЦЕПИ ПОСТОЯННОГО ТОКА - Волков , И.В.; Каршенов , Д.П. (Інститут електродинаміки НАН України, Київ, 2012)
The analytical method is used for derivation of the universal design formula of the m-pulse three phase rectifier. This formula is proposed as mathematical model of an equivalent circuit with current sources of fundamental frequency and current harmonics. References 6, tables 2, figures 4.